PROSPECTS OF AGRICULTURAL DEVELOPMENT THROUGH AGRO- TOURISM - Yusupov Ne’matillo Saidturaevich; Sharobiddinov Ahrorbek Qosimjon ugli (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract. Tourism is the most profitable industry in the international industry. According to the World Tourism Organization of the United Nations, the number of tourists traveling with touristic purposes has reached 1.5 billion (1). These data clearly indicate that the tourism sector is rapidly developing. The development of tourism was caused by the development of all types of tourism. One of such developing types of tourism is agrotourism. Agrotourism is not a new type of tourism. It has been used in Europe for about 100 years. Agricultural areas meet the needs of urban residents with their natural and cultural attractions. One type of tourism formed by this desire is agrotourism. In this study, what is agrotourism, where is it needed, the necessary conditions for the formation of agrotourism, the available opportunities, as well as the advantages of agrotourism, the topic of success in the field of agrotourism of Uzbekistan is discussed.